Engineering ultra-strong electron-phonon coupling and nonclassical electron transport in crystalline gold with nanoscale interfaces - Shreya Kumbhakar; Tuhin Kumar Maji; Binita Tongbram; Shinjan Mandal; Shri Hari Soundararaj; Banashree Debnath; Phanindra Sai T; Manish Jain; H. R. Krishnamurthy; Anshu Pandey; Arindam Ghosh (Nature Communications)
Abstract Electrical resistivity in good metals, particularly noble metals such as gold (Au), silver (Ag), or copper, increases linearly with temperature (T) for T > Θ D , where Θ D is the Debye temperature. This is because the coupling (λ) between the electrons and the lattice vibrations, or phonons, in these metals is weak, with λ ~ 0.1−0.2. In this work, we outline a nanostructuring strategy of crystalline Au where this concept of metallic transport breaks down. We show that by embedding a distributed network of ultra-small Ag nanoparticles (AgNPs) of radius ~ 1–2 nm inside a crystalline Au shell, the electron-phonon interaction can be enhanced, with an effective λ as high as  ≈ 20. With increasing AgNP density, the electrical resistivity deviates from T-linearity and approaches a saturation to the Mott-Ioffe-Regel scale ρ MIR ~ h a/e 2 for both disorder (T → 0) and phonon (T ≫ Θ D )-dependent components of resistivity (here, a = 0.3 nm, is the lattice constant of Au).